1065Diesel exposure and bladder cancer in contemporary Western Australian miners. (2nd September 2021) - Sodhi-Berry, Nita; Franklin, Peter; Peters, Susan; Reid, Alison; Musk, Arthur (Bill); Fritschi, Lin; Vermeulen, Roel; de Klerk, Nicholas
Abstract: Background: Diesel engine exhaust (DEE) is classified as a potential carcinogen for bladder cancer in humans by the International Agency for Research on Cancer. We aimed to compare bladder cancer incidence in Western Australian miners against the general population and determine if there was an association with DEE, measured as Elemental Carbon. Methods: A whole-of-population cohort of 218, 846 Western Australian miners employed during 1996-2013 was followed-up until June-2017. DEE exposure data was derived from work histories and collated with administrative State-wide cancer and death data. Standardised Incidence Ratios (SIRs) were calculated to compare rates with the general population. A nested case-control study design with matching on attained age was used. Conditional logistic regression was done to calculate Odds Ratios (ORs) for cumulative Elemental Carbon exposure (unlagged and 15-year lagged), after adjusting for smoking pack-years. Results: Ninety cases (88 males) were observed and 180, 377 controls selected. Miners had lower bladder cancer incidence than the general population (Observed=90; Expected=135.60; SIR:0.66, 95%CI:0.53-0.80). Within miners, DEE exposure was not found to be statistically significantly associated with bladder cancer (unlagged: OR = 0.75, 95%CI: 0.43-1.31; and 15-year lagged: OR = 0.59, 95%CI:0.25-1.40), after adjusting for smoking pack-years (unlagged and lagged OR:1.02, 95%CI:1.01-1.03). Conclusions: Miners had lower risk of bladder cancer than the general population. DEE exposure was not associated with bladder cancer in this nested case-control study of contemporary Western Australian miners. Key messages: Diesel engine exhaust was not found to be associated with bladder cancer in miners.